Pension incentives and formal-sector labor supply : evidence from Colombia (2017)
This paper describes how future pension benefits affect labor supply in economies that have an informal sector. From the perspective of the worker, a formal-sector job offers long-run gains, as it increases his likelihood of gaining pension benefits in the future. If workers take those gains into account when they search for formal-sector jobs, the pension system affects formal-sector labor supply. I estimate the causal link between pension incentives and formal-sector labor supply using a cohort-based reform undertaken in Colombia. I demonstrate that a change in future pension benefits generates a large shift between the formal-sector and informal-sector labor supply, and that this change does not affect labor force participation. The average effect of pension incentives on formal-sector labor supply is heterogeneous, and is consistent with the predictions of a theoretical model combining a pension system and informal job opportunities. The effect is concentrated among workers for whom the minimum qualifying conditions are binding, and among workers with higher expected pension wealth. The results presented here suggest that pension reforms have the potential to create large efficiency costs, an effect that should be taken into account when designing pension programs.